The helical domain of the EcoR124I motor subunit participates in ATPase activity and dsDNA translocation - Bialevich, Vitali; Sinha, Dhiraj; Shamayeva, Katsiaryna; Guzanova, Alena; Řeha, David; Csefalvay, Eva; Carey, Jannette; Weiserova, Marie; Ettrich, Rüdiger H (PeerJ, 2017)
Type I restriction-modification enzymes are multisubunit, multifunctional molecular machines that recognize specific DNA target sequences, and their multisubunit organization underlies their multifunctionality. EcoR124I is the archetype of Type I restriction-modification family IC and is composed of three subunit types: HsdS, HsdM, and HsdR. DNA cleavage and ATP-dependent DNA translocation activities are housed in the distinct domains of the endonuclease/motor subunit HsdR. Because the multiple functions are integrated in this large subunit of 1,038 residues, a large number of interdomain contacts might be expected. The crystal structure of EcoR124I HsdR reveals a surprisingly sparse number of contacts between helicase domain 2 and the C-terminal helical domain that is thought to be involved in assembly with HsdM. Only two potential hydrogen-bonding contacts are found in a very small contact region. In the present work, the relevance of these two potential hydrogen-bonding interactions for the multiple activities of EcoR124I is evaluated by analysing mutant enzymes using in vivo and in vitro experiments. Molecular dynamics simulations are employed to provide structural interpretation of the functional data. The results indicate that the helical C-terminal domain is involved in the DNA translocation, cleavage, and ATPase activities of HsdR, and a role in controlling those activities is suggested.
Keywords: E. coli; DNA restriction enzymes; Domain interactions; Multisubunit enzyme complex; Molecular modeling